Plasma metabolome and cognitive skills in Down syndrome - Antonaros, Francesca (Sci Rep, 2020)
Trisomy 21 (Down syndrome, DS) is the main human genetic cause of intellectual disability (ID). Lejeune hypothesized that DS could be considered a metabolic disease, and we found that subjects with DS have a specific plasma and urinary metabolomic profile. In this work we confirmed the alteration of mitochondrial metabolism in DS and also investigated if metabolite levels are related to cognitive aspects of DS. We analyzed the metabolomic profiles of plasma samples from 129 subjects with DS and 46 healthy control (CTRL) subjects by (1)H Nuclear Magnetic Resonance (NMR). Multivariate analysis of the NMR metabolomic profiles showed a clear discrimination (up to 94% accuracy) between the two groups. The univariate analysis revealed a significant alteration in 7 metabolites out of 28 assigned unambiguously. Correlations among the metabolite levels in DS and CTRL groups were separately investigated and statistically significant relationships appeared. On the contrary, statistically significant correlations among the NMR-detectable part of DS plasma metabolome and the different intelligence quotient ranges obtained by Griffiths-III or WPPSI-III tests were not found. Even if metabolic imbalance provides a clear discrimination between DS and CTRL groups, it appears that the investigated metabolomic profiles cannot be associated with the degree of ID.